MODAL SOSIAL BONDING DALAM PENGEMBANGAN KAMPUNG WISATAKREATIF DAGO POJOK KOTA BANDUNG, PROVINSI JAWA BARAT - Alfrojems, Alfrojems; Anugrahin, Triyanti (Jurnal Ilmu Kesejahteraan Sosial, 2019)
The development of a tourism village has become one of the primaries in community development, especially in rural areas, carried out either by the government or other parties. This is an effort to alleviate poverty in rural areas which is currently an area with a reasonably large amount of poverty with 15.15 million people. But the process of this development provides a dilemma and question about how the process can develop bondsin the community itself that are relevant to the context of bonding social capital. This article aims to explore information about how Dago Pojok creative tourism village community develops their bonding social capital for the sustainability development of Dago Pojok creative tourism village. This research uses a qualitative method with descriptive type. The data collection in this reseacrh is study of documentation, observation and interview. In this study, interview were conducted on 12 (twelve) informants with criteria based on purposive sampling. The results of this study found that there were efforts made by the community to continue to develop bonding social capital which embedded to the community